الأمن الأسري زمن النزاعات المسلحة من خلال قواعد الشريعة الإسلامية والقانون الدولي الإنساني - حمزة, نصرات; نورالدين, مناني (جامعة الوادي university of eloued, 2023)
تتناول هذه الدراسة موضوعا مهما يتعلق بأمن الأسرة من خلال قواعد النزاعات المسلحة في الشريعة الإسلامية والقانون الدولي الإنساني؛ حيث يوجد العديد من المبادئ والوسائل المهمة التي تؤسس لأمن الأسرة وتدعم حمايتها واستقرارها، ولعل من أهم هذه المبادئ مبدأ التمييز ومبدأ الإنسانية وكذلك صيانة الحرمات، أما الوسائل فإنّ منها ما هو عام كالالتزام بتعليمات قواعد النزاعات المسلحة ونشرها واحترامها والأخذ بالتدابير الوقائية وأعمال الإغاثة، ومنها ما هو خاص كحفظ الأسرة من التفكك وجمع شملها بعد التشتت وحماية السكن العائلي، ومراعاة الخصوصية لبعض أفراد الأسرة، وكانت أهم النتائج المتوصل إليها، أن الأسرة الأسرة كيانا مهما جدا وجب الاهتمام به في كل الظروف، سواء حال الحرب أو السلم. This study deals with an important topic related to family security through the rules of armed conflicts in Islamic law and international humanitarian law. Where there are many important principles and means that establish family security and support its protection and stability, and perhaps the most important of these principles is the principle of discrimination and the principle of humanity as well as the maintenance of sanctities. It is special, such as preserving the family from disintegration, reuniting it after dispersal, protecting family housing, providing family units, and taking into account the privacy of some family members. The most important results reached were that the family is a very important entity that must be taken care of in all circumstances, whether war or peace
مقال
Keywords: الأمن الأسري؛ النزاعات المسلحة؛ القانون الدولي الإنساني; Family security. Armed conflicts. International humanitarian law